Fixed start method for repetitive project scheduling with simulated annealing - Francisco Moreno; Eric Forcael; Francisco Orozco; Felipe Baesler; Duzgun Agdas (Heliyon)
This research deals with the high project completion variability by presenting a new method to decrease such variability in repetitive construction projects. To achieve this, a Fixed Start Method (FSM) —where the starts of each activity with a high level of probabilistic confidence for the planned project duration are fixed— was applied, where the high level of probabilistic confidence obtained was optimized with the use of the metaheuristic algorithm called Simulated Annealing (SA). This procedure evaluated the project completion in a case study based on the coefficient of variance (COV) of the resulting standard deviation, mean, and temperature selected for the SA. Thus, the combined FSM and SA (FSSA) is a new method that decreases the variability of scheduling duration while achieving project completion times. Finally, the proposed FSSA method for construction scheduling was validated in a case study using Discrete Event Simulation.